Management of elective procedures in low von Willebrand factor patients in the LoVIC study. (24th January 2021) - Doherty, Dearbhla; Lavin, Michelle; O'Sullivan, Jamie M.; Ryan, Kevin; O'Connell, Niamh M.; Dougall, Alison; Byrne, Mary; Rafferty, Marie; Doyle, Mairead M.; Di Paola, Jorge; James, Paula D.; O'Donnell, James S.
Abstract: Background: Most individuals with mild to moderate reductions in plasma von Willebrand factor (VWF) levels do not demonstrate increased bleeding. However, some patients with plasma VWF levels of 30–50 IU/dl do have a significant bleeding phenotype. Management of these "low VWF" patients, who may have significant bleeding scores >10, around times of elective procedures continues to pose a common clinical challenge because of a lack of evidence. Objective: To investigate the safety and efficacy of different periprocedural management options for adult patients with low VWF. Methods: Treatment and outcomes were retrospectively reviewed for 160 invasive procedures performed in 60 patients with well characterized low VWF enrolled in the previously described Low Von Willebrand factor Ireland Cohort study. Results: We demonstrate that 1‐desamino‐8‐D‐arginine vasopressin is efficacious in preventing bleeding for both minor or major elective procedures in adult low VWF patients, even in those with significant bleeding histories. In addition, tranexamic acid alone is effective for low VWF patients undergoing nondental minor procedures. Importantly, age‐related increases in plasma VWF:antigen levels above 50 IU/dl were not necessarily associated with complete correction of bleeding phenotype. Procedure‐related bleeding complications were increased in low VWF patients who did not receive any hemostatic cover before their procedure. Conclusion: Elective procedures in adult patients with low VWF should be managed in liaison with a comprehensive care tertiary referral center so that personalized treatment plans may be implemented before all minor or major elective procedures.